Innovation in Early Childhood Vocal Technique Learning through Interactive Music Activities - Riau Wika; Ramadhina, R. Mekar Liza (Journal of Arts Education and Design, 2025)
This study discusses the implementation of interactive musical activities in vocal technique learning for early childhood. The main issue addressed is how musical activities can help children understand and master basic vocal techniques through enjoyable experiences that suit their developmental stage. The purpose of this research is to describe the forms of interactive musical activities in learning vocal techniques, which include body posture, breathing, intonation, articulation, resonance, dynamics, and reflection, as well as their impacts on the vocal abilities of young children. The study employs a qualitative descriptive approach through observation of the vocal learning process in early childhood. The results show that each vocal technique provides different benefits: proper body posture supports good singing habits, breathing exercises train voice control, articulation improves lyric clarity, intonation enhances pitch sensitivity, resonance enriches vocal tone quality, while dynamics and expression help children convey emotions in their singing. Interactive musical activities are proven effective in helping children learn vocal techniques in an engaging, active, and developmentally appropriate way. Keywords: Interactive Musical Activities, Vocal Technique Learning, Early Childhood